ANTIFUNGAL ACTIVITY OF A PHOSPHORYLATED 3-(α-HYDROXYALKYL) ALLENES ETHANOL EXTRACTS - Sevginar Ibryamova; Hasan Hasanov; Tsveteslava Ignatova-Ivanova (Peytchinski Publishing, 2020)
yeast and fungi had been established. PA-2 (50mg/ml, 25mg/ml, 12.5mg/ml, 6.25mg/ml and 3.125mg/ml) exerted different inhibitory effect on different yeast and fungi cells in vitro. The effects of PA-2 on eukaryotic cells have not been studied yet. The present study was aimed to assess the antifungal activity of PA-2on pathogenic yeast and fungi. Experimental approach: In vitro antifungal test: Aspergillus niger, Penicillium claviforme, Saccharomyces cerevisae, Candida albicans 8673 and Candida glabrata 72 were treated for 24 hours with PA-2(50mg/ml, 25mg/ml, 12.5mg/ml, 6.25mg/ml and 3.125mg/ml), Fluconazole (150 mg/ml). The antifungal activity was assayed by the gootiffusion method with a digitalaliper. Determination of minimum inhibitory concentrations (MICs): The MIC of PA-2, that shows antifungal activity wasetermined by 2-fold dilution methodsnd MICs were read in μg/ml after overnight incubation at 37ºC. Determination of Minimum fungal concentration (MFC): The MFC was carried out to check whether the test microbes were killed or only their growth was inhibited. Potato Dextrose Agar (PDA, Oxoid, Hampshire, UK) was prepared and sterilized at 121ºC for 15 minutes, the medium was poured into sterile petri dishesnd was allowed to cool and solidify. The contents of the MIC in the serial dilution were then subcultured onto the prepared medium, incubation was made at 37ºC for 24 h, after which each plate was observed for colony growth. All experiments were performed in triplicate. The lowest concentration of the PA-2 without a colony growth was recorded as the MFC. PA-2 had higher antifungal activity than the tested antibiotic (Fluconazole).